Pengaruh Whisper Chain Game Berbasis Cerita Kearifan Lokal Terhadap Peningkatan Hasil Belajar Dalam Pembelajaraan Ipas Siswa Kelas V Sekolah Dasar Upt Spf Sd Inpres Laikang Makassar - Nur Tiara Sakina (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aimed to examine the effect of the Whisper Chain Game learning method based on local wisdom stories on the Natural and Social Sciences (IPAS) learning outcomes of fifth-grade students at UPT SPF SD Inpres Laikang Makassar. This study employed a quantitative approach using a quasi-experimental design with a Nonequivalent Control Group Design. The sample consisted of 55 students, including 26 students in the experimental class and 29 students in the control class. Data were collected through observation, tests, and documentation and analyzed using descriptive and inferential statistics, including normality and homogeneity tests, N-Gain analysis, and the Mann–Whitney U test. The findings indicated that the implementation of the Whisper Chain Game based on local wisdom stories was categorized as very good. The mean score of the experimental class increased from 47.50 to 80.96, while the control class improved from 45.69 to 68.85. The average N-Gain score of the experimental class (0.607) was higher than that of the control class (0.439), although both were classified as moderate. The Mann–Whitney U test yielded a significance value of 0.011 (p < 0.05), indicating a statistically significant effect of the Whisper Chain Game based on local wisdom stories on students' IPAS learning outcomes.